ESTIMASI MUSIM PENANGKAPAN LAYANG (DECAPTERUS SPP) YANG DIDARATKAN DI PPN PEKALONGAN, JAWA TENGAH - Ronny Irawan Wahju; Zulkarnain Zulkarnain; Karina P Sangara Mara (Buletin PSP, 2011)
Estimation fishing season of layang (Decapterus spp) was carried out through data catch of layang from purse seine fishing units landed at PPN Pekalongan. The objectives of the research were to analyze the trend of catch per unit effort of layang (CPUE), to estimate the pattern of fishing season and fishing ground of layang. CPUE analysis was carried out by comparing the catch of fishing effort, the estimated pattern of fishing season was carried out by analysis of time series (moving average), and estimates of the fishing ground by ranking the value of the average monthly trip. During 2004 to 2008, the average CPUE of layang is 13.55 tonnes/trip to the range of 1.37 to 39.60 tons/trip. Fishing season layang is in January, February and May to December, peak season in November and off season in March. Potential fishing ground for catching layang was estimated at Lumu-lumu, South China Sea, Bawean, Matasiri and Karimun-Cirebon.